Analysis of the Root Cause of Delays in Delivery of Export Cargo with Incoterms Free On Board at PT. Vifiera Minova Brothers Using the Fish Bone Diagram Method - Yunanto, Dwi; Putri, Rehita Ayunda; Sari, Damara Kartika; Rachman, Adelia Nasya (Majalah Ilmiah Bijak, 2025)
Delays in the delivery of goods in export cargo containers are a problem that is often faced by business people, especially those who use Free on Board incoterms. This delay has a significant impact on customer satisfaction. Therefore, it is important to conduct an in-depth analysis of the factors that contribute to or even become the root of the problem. The purpose of this study is to analyze the root cause of delays in the delivery of export cargo goods using containers with inconterm free on board using the fish bone diagram method. By identifying and grouping these causes into relevant categories. This research was conducted using a qualitative method, with descriptive data analysis techniques. The data obtained from the results of this study were processed and analyzed using the Fish Bone Diagram method. The results of this study show that the main factor causing frequent delivery delays is during the process of picking up empty containers at the depot.